ANALISIS FRAUD PENTAGON THEORY DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Reynaldi Surya Prayonggie; Yohanes Yohanes (Universitas Trilogi, 2022)
This study aims to obtain empirical evidence and analyze the effect of financial stability, external pressure, change of directors, financial targets, ineffective monitoring, nature of industry, frequent number of CEO's picture. The number of samples used in this study is 198 data from 66 manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2020 using the purposive sampling method in the sampling process. This study uses multiple regression methods in order to explain the effect of independent variables on the dependent variable of fraud on financial statements. The greater the external pressure, the less likely there is to be fraudulent financial statements. The bigger the financial target, the lower the fraud on the financial statements. The higher the level of nature of the industry, the difficulty in fraud on financial statements will occur. The novelty of this research is the addition of ineffective monitoring, financial target variables and the frequent number of CEO's picture. This research is expected to contribute to the development of theories, especially those related to fraudulent acts on financial statements such as fraud diamonds, fraud pentagons, and signaling theory and can contribute to developing variables used in further research.